European individuals’ satisfaction with national governments during the COVID-19 pandemic - Erdal Eren Kizilirmak; Erdem Kilic (Discover Global Society)
Abstract Our study investigates Europeans’ satisfaction with national governments from 2020 to 2022 during the COVID-19 pandemic, using data from Round 10 of the European Social Survey. Using two econometric models, the study explores factors associated with satisfaction, including healthcare services, political ideology, political participation, and demographic factors such as household income, gender, unemployment, generation, and education. Findings reveal a strong correlation between healthcare satisfaction and satisfaction with the national governments. Furthermore, political ideology, unemployment, gender, and generational differences are significantly associated with satisfaction levels with national governments, either positively or negatively.